Digital Literacy of Elementary Teachers and its Relation to Performing their Various School Roles Amidst COVID-19 Pandemic - Pizarro, Marlon; Caballes, Dennis; Vianzon, Jerwin (Journal of Interdisciplinary Perspectives, 2024)
Amidst the lengthy suspension of in-person classes brought by the unprecedented pandemic of Coronavirus Disease 2019 (COVID-19), widespread adoption of digital technology in education has become critical. However, there is a growing global worry about teachers' digital literacy. The purpose of this study, which was done in four core schools in Bataan's second congressional district, Philippines, is to investigate public elementary school teachers' digital literacy and its impact on the various duties and responsibilities they take on. The study included 225 teachers, four ICT coordinators, and four school leaders from the identified central schools. There were significant disparities in the assessment of digital literacy and performance among the three groups of respondents (teachers, ICT coordinators, and school principals). Furthermore, while there was no significant association established between teachers' characteristics (including age and sex) and their digital literacy, a substantial relationship was discovered between teachers' digital literacy and their overall performance. This study provides useful insights into the landscape of digital literacy among elementary teachers during the COVID-19 pandemic, with implications for educational policies, professional development, and the efficient integration of digital tools in many school roles.